HIV/AIDS in Nepal: Trends, Barriers, Challenges and Strategic Responses - Shah, Debi Kumari (Journal of Deukhuri Multiple Campus, 2026)
Human Immunodeficiency Virus/Acquired Immunodefic iency Syndrome (HIV/AIDS) continues to pose a significant public health challenge in Nepal. The epidemic disproportionately impacts key populations, including female sex workers, men who have sex with men (MSM), people who inject drugs (PWID), and migrant workers. Despite commendable progress in expanding antiretroviral therapy (ART) services and increasing HIV testing coverage, the national response is continually hampered by pervasive systemic and structural barriers that impede equitable and sustainable outcomes. This study aims to provide a critical assessment of the current epidemiological status of HIV/AIDS in Nepal and to meticulously examine the major challenges that obstruct effective prevention, treatment, and control efforts. Employing a qualitative and descriptive methodology, this investigation synthesizes evidence from authoritative secondary sources, including government surveillance data, national policy documents, and peer-reviewed academic literature. The analysis reveals critical gaps in service delivery, widespread social stigma, a notable deficit in comprehensive sexual and reproductive health education, and persistent inequities in access to care, particularly affecting rural and marginalized communities. The findings indicate that while Nepal has achieved measurable advancements, high-risk populations remain underserved due to a complex interplay of sociocultural discrimination, geographic isolation, and limited health system capacity. Furthermore, migrant workers experience heightened vulnerability, often stemming from inadequate pre-departure education and a lack of reintegration services upon their return. The study concludes that an effective response to HIV/AIDS in Nepal necessitates a rights-based, community-driven, and multisectoral approach. This includes scaling up stigma-reduction initiatives, integrating HIV education into both school curricula and public outreach programs, expanding community-based services, and enhancing surveillance for data-driven policymaking. Only through such inclusive and targeted interventions can Nepal aspire to achieve long-term epidemic control and foster improved health equity among its vulnerable populations.